Measuring Local Mechanical Properties Using FIB Machined Microcantilevers - Armstrong, D; Wilkinson, A; Roberts, S (2009)
Micro-scale Focused Ion Beam (FIB) machined cantilevers were manufactured in single crystal copper, polycrystalline copper and a copper-bismuth alloy. These were imaged and tested in bending using a nanoindenter. Cantilevers machined inside a single grain of polycrystalline copper were tested to determine their (anisotropic) Young's modulus: results were in good agreement with values calculated from literature values for single crystal elastic constants. The size dependence of yield behavior in the Cu microcantilevers was also investigated. As the thickness of the specimen was reduced from 23μm to 1.7μm the yield stress increased from 300MPa to 900MPa. Microcantilevers in Cu-0.02wt%Bi were manufactured containing a single grain boundary of known character, with a FIB-machined sharp notch on the grain boundary. The cantilevers were loaded to fracture allowing the fracture toughness of grain boundaries of different misorientations to be determined. © 2009 Materials Research Society.